Lactobacillus rhamnosus CRL1505 and its peptidoglycan as enhancers of antiviral respiratory immunity - Kolling, Yanina Noralí (2013)
The effect of nasally administered Lactobacillus rhamnosus CRL1505 and its peptidoglycan (Pg) on respiratory antiviral immunity triggered by poly(I:C) was studied. Mice were nasally treated with viable (LV) or heat killed (LH) CRL1505 strain or Pg for 2d. Then, these groups and untreated control mice were nasally challenged with 3 daily doses of poly(I:C) (250 μg/mouse). INFγ, IFNβ, IFNα, TNFα, IL6, IL10 in bronchoalveolar lavage (BAL) and serum, expression of CD3, CD4, CD11b, CD11c, CD103, MHCII, IL10 and INFγ in lungs, and lung injury were determined. Poly(I:C) increased the levels of all the evaluated cytokines, accompanied by the recruitment of immune cells into the lung. In addition, increased protein content and LDH activity in BAL and altered lung wet weight:dry weight ratio were observed, indicating increased permeability of the alveolar-capillary barrier and lung injury. LV, LH or Pg administration enhanced INFγ, IFNβ and IL6 production and increased MHCII+CD103+, MHCII+CD11b+ dendritic cells and CD4+INFγ+and CD4+IL10+lymphocytes in lungs. Mice treated with LV, LH or Pg showed lower lung tissue damage. Results show that nasal administration of non-viable Lr1505 or its Pg maintains the probiotic properties of the viable strain and therefore they could be used to beneficially modulate the antiviral inflammatory response in the respiratory mucosa.